2018
DOI: 10.1021/acs.analchem.8b02133
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting Glioma Perivascular Niches on a Chip for Insights into Chemoresistance of Glioma

Abstract: In this work, we report the direct diagnosing chemoresistance of glioma stem cells (GSCs) during chemotherapy on a biomimetric microsystem that reconstitutes glioma perivascular niches on a chip. Glioma stem cells and endothelial cells were specially cocultured onto the biomimetric system to precisely control stem cell coculture for the proof-of-principle studies. The expression levels of 6- O-methylguanine was confirmed by mass spectrometer, and Bmi-1 gene was also investigated to uncover the chemoresistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…In normal brain, most of CHIP protein was expressed in the cytoplasm of neurons. Moreover, CHIP is a key regulator of glioma progression, as evident by the fact that ChIP overexpression can promote the colony formation and proliferation of glioma cell lines in vitro, while CHIP knockdown can achieve the opposite result; and a consistent result was obtained by in vivo experiment 26 . These results indicate that CHIP is necessary for tumorigenesis and can induce the tumorigenesis of human glioma.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In normal brain, most of CHIP protein was expressed in the cytoplasm of neurons. Moreover, CHIP is a key regulator of glioma progression, as evident by the fact that ChIP overexpression can promote the colony formation and proliferation of glioma cell lines in vitro, while CHIP knockdown can achieve the opposite result; and a consistent result was obtained by in vivo experiment 26 . These results indicate that CHIP is necessary for tumorigenesis and can induce the tumorigenesis of human glioma.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, CHIP is a key regulator of glioma progression, as evident by the fact that ChIP overexpression can promote the colony formation and proliferation of glioma cell lines in vitro, while CHIP knockdown can achieve the opposite result; and a consistent result was obtained by in vivo experiment. 26 These results indicate that CHIP is necessary for tumorigenesis and can induce the tumorigenesis of human glioma. However, it has been found that CHIP has the characteristics of oncogene in some tumors, and it can also play the role of tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 85%
“…Lin et al elucidated that endothelial cells in the perivascular microenvironment promote resistance to drug response of glioma stem cells (GSC), which was challenging to show in conventional 2D culture environments that do not recapitulate interactions of endothelial cells and glioma cells [ 46 ]. Accordingly, GSCs could be treated in the nature-mimicking glioma PVN on the microdevice while maintaining cancer stem cells at the multipotent status owing to cell-cell communications.…”
Section: Glioma-on-chip Platformsmentioning
confidence: 99%
“…In the case of treatment of the GSCs by TMZ, 7-methylguanine (7-MeG) and 6-O-methylguanine (6-O-MeG) are the two biomarkers of chemoresistance diagnosis [ 22 ]. Using the proposed OOC platform, the expression levels of 7-MeG and 6-O-MeG culture were observed to be higher than cocultured GSCs, highlighting the role of endothelial cells in chemoresistance and glioma therapies [ 46 ].…”
Section: Glioma-on-chip Platformsmentioning
confidence: 99%
“…Chemoresistance of glioma was studied by analyzing the metabolism of temozolomide in an artificial glioma perivascular niche. 99 Chemoresistance of temozolomide on glioma stem cells and the molecular metabolism was investigated by an ESI-MS. Microfluidic chips provide a simulated microenvironment for cells, while MS provides the possibility for high-throughput detection. Metabolism and its kinetic of 8 drugs are evaluated, by coupling of a liver chip and MS. Hepatic clearances were extrapolated on this strategy.…”
Section: Drug Screeningmentioning
confidence: 99%